2017
DOI: 10.1146/annurev-bioeng-071516-044435
|View full text |Cite
|
Sign up to set email alerts
|

Objective Assessment of Surgical Technical Skill and Competency in the Operating Room

Abstract: Training skillful and competent surgeons is critical to ensure high quality of care and to minimize disparities in access to effective care. Traditional models to train surgeons are being challenged by rapid advances in technology, an intensified patient-safety culture, and a need for value-driven health systems. Simultaneously, technological developments are enabling capture and analysis of large amounts of complex surgical data. These developments are motivating a “surgical data science” approach to objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 122 publications
0
56
0
1
Order By: Relevance
“…Besides saving time and money, this would enable novice surgeons to train effectively in absence of a human supervisor using a surgical simulator that is equipped with automatic assessment and feedback functionalities. Consequently, objective computer-aided technical skill evaluation (OCASE-T) [28] has received increasing interest in the research community over the last decade.…”
mentioning
confidence: 99%
“…Besides saving time and money, this would enable novice surgeons to train effectively in absence of a human supervisor using a surgical simulator that is equipped with automatic assessment and feedback functionalities. Consequently, objective computer-aided technical skill evaluation (OCASE-T) [28] has received increasing interest in the research community over the last decade.…”
mentioning
confidence: 99%
“…During these simulations, monitoring the workflow of training sessions provides important data on surgical skill and on the individual surgeon's technique [44]. On the low-level (gestures) it has been shown that fine-motor skills correlate with indecisiveness of the surgeon [45], while task level assessment can be used for both skill evaluation and for designing individual training curriculas [46], [47], [48].…”
Section: Surgical Trainingmentioning
confidence: 99%
“…Egy kutatás szerint a laparoszkópos szimulátorokon megtanult és begyakorolt készségek az artroszkópos készségekre szintén hatással vannak, azokat javítják [24]. Egy 45 publikációt felölelő tanulmány szerint sebészeti készségfelmérésnek a valós műtétek során is meg kell jelennie, illetve nagyobb hangsúlyt kell fektetni a szimulátorokon való gyakorlás valós műtéti eredmé-nyekre gyakorolt hatásának nyomon követésére [25]. Egy másik kutatás szerint a laparoszkópos készségek ön-álló kiértékelésének eredménye a laparoszkópos cholecystectomiában használatos alapkészségek szimulátoros gyakorlása esetében erősen korrelál a külső, tapasztalt megfigyelők által megítélt eredménnyel.…”
Section: Megbeszélésunclassified